PARADIGMA PROSES PEMBELAJARAN MELALUI QS. AL-ALAQ DALAM MENGUATKAN KOMPETENSI PEDAGOGIK - Aam Abdussalam; Nurti Budiyanti (Universitas Pendidikan Indonesia, 2021)
AbstactThis article tries to formulate the paradigm of the learning process through Qs. Al-Alaq in strengthening pedagogic competence. Pedagogic competence is a competency that an educator must possess. Educators are one of the keys to achieving educational success. Al-Quran has very different and extraordinary characteristics, both in terms of content, language and systematics. Al-Quran has provided the best solution for all aspects of human life without the limitations of space and time, especially in the area of education. With a literature review approach, the study results show that Iqra 'as a learning paradigm, contains at least three main ideas. First, recognising human existence as learning creatures and second, recognising all entities (concrete and abstract) and all verses (quraniyyah and kauniyhay) as a source of learning and learning. Third, the recognition of tauhîdullâh as the main principle of learning development. The concept of iqra' gave birth to the idea of ta'lîm, which is closer to the meaning of